Studying the Role of Ion Migration on Perovskite Light-Emitting Diodes by Steady-State Approach - Paria Forozi-Sowmeeh; Mohammad Zohorfazeli; Morteza Maleki; Mehran Minbashi; Elnaz Yazdani (AUT Journal of Electrical Engineering)
Despite the rapid development of Perovskite-based Light-Emitting Diodes (PeLEDs) within the last decade, the role of ion migration on the operation of the devices has not been completely understood. Affecting PeLED's operation is considered as the most complicated and mysterious process. It is widely accepted that the ion migration, as an intrinsic phenomenon, is one of the main origins for low stability of PeLEDs. On the other hand, the defect passivation caused by mobile ions gives rise to enhanced charge injection from the electron and hole transporting layers, leading to more efficient light-emitting diodes. Therefore, it is critical to have a comprehensive insight to the underlying principles of ion migration and its contributing factors. In this paper, the ion migration phenomenon and its influence on the operation of a PeLED are surveyed using the Finite Element Method (FEM) simulation. The accumulation of anions and cations at the hole and electron transporting layer's interface with the perovskite facilitates hole and electron injection, which result in more carrier density favoring the radiative recombination. Therefore, ion migration is a phenomenon that is closely related to the operation and stability of the device by controlling which more stable PeLED is attainable. Our results provide a better understanding of the physics behind the ion migration, which is the first step to design more efficient devices.